Citizenship education in Portugal - Anabela Moura; Teresa Gonçalves (Escola Superior de Educação de Paula Frassinetti, 2015)
This article discusses citizenship education in Portugal and evaluates related theory and practice in art education in an Initial Teacher Training Course in Portugal, addressing the following issues: (i) the consideration of Portuguese art education practices in the context of Education for Democratic Active Citizenship provision; (ii) the recognition of problems in art education in some Portuguese schools about 'looking from oneself' to other ways of doing things because of the ethnocentric model in which many art teaching practices continue to be based, and the European attitudes  towards globalization and cultural exchanges and that these have inhibited the professional development in art education; and lastly (ii) To take a brief look at Creative Connections International Project and how its  strategies for achieving a citizenship perspective, through contemporary art,  were used in an initial teacher education course in the School of Education of Viana do Castelo -ESEVC